Reinforced and toughened carbon nanotube modified polypropylene resin and fiber composite material thereof
By using multi-scale collaborative reinforcement technology of carbon nanotubes and chopped glass fibers in polypropylene resins, the problem of insufficient improvement of mechanical properties of existing polypropylene composite materials is solved, the high strength and high toughness of fiber composite materials is achieved, and the preparation process is simplified.
Patent Information
- Application Number
- CN202411828421.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The existing polypropylene composite materials have the disadvantages of single performance improvement, limited improvement range, poor filler dispersion in terms of mechanical properties, and are complex in operation and harsh conditions, which affect application promotion.
The polypropylene resin is enhanced by multi-scale multi-scale synergistically by using carbon nanotube fillers and chopped glass fibers. The uniform dispersion of carbon nanotubes in the polypropylene resin matrix is achieved through the synergistic action of cetyl trimethylammonium bromide and γ-aminopropyl triethoxysilane, and the mechanical properties of the material are improved through the melt blending process.
It significantly improves the overall mechanical properties of fiber composite materials, enhances the tensile strength, bending strength and short beam shear strength of the material, and improves the forming quality and use range of materials.
Smart Images

Figure CN119798907A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of polypropylene-based fiber composite materials, in particular to a reinforced and toughened carbon nanotube-modified polypropylene resin and a fiber composite material thereof. Background Art
[0002] Polypropylene is a thermoplastic with light specific gravity, high surface hardness and high elasticity. It is widely used due to its excellent chemical stability and processing characteristics, and is widely used in automotive parts, household appliances, medical and health fields. However, polypropylene still has defects such as weak low-temperature impact strength, easy aging, and poor electrical and thermal properties, which limit its scope of application. In order to enhance the mechanical properties of current polymer materials, adding talcum powder, mica powder, glass fiber and other inorganic fillers has become a means of extensive research and application, but due to the constraints of inorganic particle size and dispersion characteristics, the improvement of the mechanical properties of polymer composites is limited. Compared with inorganic fillers, nano-scale fillers have a relatively high specific surface area and can increase the active interface with the polymer, and are considered to be one of the effective ways to improve the comprehensive performance of polypropylene.
[0003] In the prior art, China Publication No.: CN109608669A discloses a carbon nanotube-enhanced polypropylene composite material, wherein the carbon nanotube array is subjected to a graft polymerization reaction with a polypropylene resin M1 to obtain a modified carbon nanotube, and then the modified carbon nanotube is melt-mixed with a polypropylene resin M2 to obtain a polypropylene composite material, which effectively improves the mechanical properties of polypropylene. China Publication No.: CN 108794885A discloses an anti-aging and impact-resistant modified polypropylene material and a preparation method thereof, wherein a polypropylene resin, p-alkoxyphenol, polymerized rosin and nano-titanium dioxide are blended to obtain a modified polypropylene material, wherein the synergistic effect of p-alkoxyphenol and polymerized rosin causes tertiary carbon radicals to migrate to p-alkoxyphenol in time, thereby preventing reactions between molecular chains and improving the anti-aging property of polypropylene; and the impact strength of the material is effectively improved by directional crystallization into a β-crystal form during crystallization. China Publication No.: CN 109796679A discloses a two-dimensional ultra-thin titanium dioxide modified polypropylene nanocomposite material. The prepared ultra-thin titanium dioxide sheet has an ultra-high specific surface area and is used to modify polypropylene to significantly improve the weather resistance and toughness of the polypropylene matrix, thereby expanding the outdoor service life and application range of polypropylene products.
[0004] However, the polypropylene composite materials prepared above generally have the disadvantages of single performance improvement, limited improvement, poor dispersion of fillers, etc., and the operation is complicated and the conditions are harsh, which seriously affects their application and promotion. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a reinforced and toughened carbon nanotube-modified polypropylene resin, which effectively improves the problem of difficulty in impregnation caused by the high viscosity of the polypropylene matrix in the molten state, and at the same time, sufficient melting time eliminates most of the pores, cracks and other internal defects in the fiber composite material.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A reinforced and toughened carbon nanotube modified polypropylene resin is prepared by the following steps, wherein the formula is calculated by weight: 0.5-2 parts of carbon nanotube filler (solid), 1-6 parts of polyvinyl pyrrolidone (solid, dispersant), 0.5-2 parts of hexadecyltrimethylammonium bromide (liquid, surfactant), 0.5-1.5 parts of γ-aminopropyltriethoxysilane (silane coupling agent), 2-6 parts of chopped glass fibers (solid), 0.5-1.5 parts of ethylene-octene copolymer (solid, toughening agent), 0.05-0.15 parts of 3,3',5,5'-tetramethylbenzidine (solid, toughening agent) and 90-100 parts of maleic anhydride grafted polypropylene (solid);
[0008] Step 1: preparing a carbon nanotube reinforcement: polyvinyl pyrrolidone, γ-aminopropyl triethoxysilane and anhydrous ethanol are stirred and mixed according to a ratio, a carbon nanotube filler is added to the mixed solution, and an ultrasonic treatment is used to obtain a uniform mixed solution to obtain a carbon nanotube dispersion I; hexadecyl trimethyl ammonium bromide is added, and the carbon nanotube dispersion I is dispersed by high-speed centrifugation, and allowed to stand to obtain a stratified carbon nanotube dispersion II; the upper layer solution is extracted to obtain a carbon nanotube dispersion III placed in a lower layer; the carbon nanotube dispersion III is filtered with a membrane filter, and the precipitate is washed and dried to obtain a carbon nanotube reinforcement IV modified by adsorption of hexadecyl trimethyl ammonium bromide;
[0009] Step 2: Prepare a reinforced and toughened carbon nanotube modified polypropylene resin: add ethylene-octene copolymer, maleic anhydride grafted polypropylene, chopped glass fiber, and 3,3',5,5'-tetramethylbenzidine into a twin-screw extruder according to a ratio, mix them evenly in the hopper of the twin-screw extruder, and add the carbon nanotube reinforcement IV, and obtain a reinforced and toughened carbon nanotube modified polypropylene resin by melt blending and extrusion.
[0010] Preferably, the carbon nanotube filler is a carboxyl carbon nanotube with a size of 5-20 nm; and the length of the chopped glass fiber ranges from 10-50 μm.
[0011] Preferably, the carbon nanotube dispersion I is a mixed dispersion of carbon nanotube fillers in polyvinyl pyrrolidone and anhydrous ethanol. Polyvinyl pyrrolidone is easily soluble in anhydrous ethanol due to similar polarity. The formed mixed solution provides a dispersion medium for the carboxyl carbon nanotube filler, and the carbon nanotube filler is evenly dispersed in combination with ultrasonic treatment; the power of the ultrasound is 200-400W, and the time is 0.5-1h.
[0012] Preferably, hexadecyltrimethylammonium bromide modifies carbon nanotubes by π-π bonds and hydrogen bonds, the carbon nanotube solid particles carry negative charges in the hydrophilic medium, and hexadecyltrimethylammonium bromide interacts with the π electrons on the surface of the carbon nanotubes to form a strong adsorption layer on the surface of the carbon nanotubes to form modified carbon nanotubes, while excess hexadecyltrimethylammonium bromide is dispersed in anhydrous ethanol solvent; the centrifugal dispersion time is 10-60 min, and the centrifugal speed is 8000-20000 rpm.
[0013] Preferably, the upper layer solution of the carbon nanotube dispersion II is anhydrous ethanol, and the lower layer solution is a mixed dispersion of carbon nanotube filler, hexadecyltrimethylammonium bromide and polyvinyl pyrrolidone.
[0014] Preferably, the carbon nanotube reinforcement IV is obtained by washing the carbon nanotube dispersion II with distilled water to obtain a precipitate, and then drying it at 25-80° C. for 18-30 hours.
[0015] Preferably, in step 2, the rotation speed of the twin-screw extruder high-speed mechanical shear stirring is 1000-3000 rpm, the stirring temperature is 190-240°C, and the nozzle temperature is 190-200°C.
[0016] Preferably, in step 2, the ethylene-octene copolymer is distributed in the continuous phase polypropylene matrix in the form of microfibrillated particles, and the 3,3',5,5'-tetramethylbenzidine induces the polypropylene matrix to form β crystals during the cooling process of melt blending, generating slender rod-shaped crystals; when subjected to impact damage, the applied impact stress is evenly diffused along the toughening particles, so that the stress acting on the brittle polypropylene matrix is reduced, and a large number of silver streaks and shear bands are induced in the matrix, thereby absorbing most of the impact kinetic energy, and achieving matrix toughening of the fiber composite material.
[0017] Another object of the present invention is to provide a polypropylene-based fiber composite material prepreg tape, which is prepared by a reinforced and toughened carbon nanotube-modified polypropylene resin as described above, and its preparation method is as follows: continuous fibers are driven by a traction system to pass through a creel, and are dispersed into continuous fiber monofilaments through dispersion, preheating desizing, and yarn spreading treatment; the molten reinforced and toughened carbon nanotube-modified polypropylene resin extruded by a twin-screw extruder is spread on the surface of the fiber filaments, and the resin is impregnated into the fiber through a melt impregnation mold; and the polypropylene-based fiber composite material prepreg tape is obtained through calendering treatment.
[0018] Preferably, the continuous fibers are glass fibers, carbon fibers or basalt fibers, with a heating melting temperature of 230-270° C. and a pulling rate of 0.1-0.5 m / min.
[0019] Another object of the present invention is to provide a polypropylene-based fiber composite material, which is prepared by a polypropylene-based fiber composite material prepreg tape as described above, and the preparation method is as follows: the polypropylene-based fiber composite material prepreg tape is passed through a yarn frame under the drive of a traction system, heated and melted in a melting mold, cooled and shaped, and pultruded to obtain a polypropylene-based fiber composite material.
[0020] Preferably, the molding temperature is 200-250°C, the cooling temperature is 80-150°C, and the pulling speed is 0.1-0.5 m / min.
[0021] Preferably, the polypropylene-based fiber composite material is pultruded into a fiber composite material profile of corresponding shape and specification according to the shape at the outlet of the internal cavity of the melting mold.
[0022] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0023] 1. The carbon nanotube particles are uniformly dispersed in the polypropylene resin matrix through the synergistic effect of the non-covalent bond modification of hexadecyltrimethylammonium bromide and the grafting of γ-aminopropyltriethoxysilane. On the one hand, the cationic surfactant hexadecyltrimethylammonium bromide is a polar molecule containing an alkyl hydrophobic end and an ammonium bromide hydrophilic end. It can be strongly adsorbed on the surface of carbon nanotube particles through the π-π bond electrostatic effect, forming a hydrophilic layer on the surface of carbon nanotube particles, and forming hydrogen bonds between the hydrophilic end and the polar solvent; on the other hand, γ-aminopropyltriethoxysilane is grafted on the surface of carbon nanotubes through a hydrolysis reaction with the end group of the carbon nanotube filler, generating hydroxyl and amino groups on the surface, and also forming hydrogen bonds with the polar solvent, which jointly promote the dissolution and uniform dispersion of the carbon nanotube filler.
[0024] 2. The flow characteristics of the polypropylene matrix during melt blending cause the orientation of the chopped glass fibers. Most of the chopped glass fibers tend to be oriented along the direction of the extruded melt flow, which is beneficial to the reinforcement of the polypropylene matrix along the extrusion direction; the uniform dispersion of the carbon nanotube filler improves the adhesion of the carbon nanotube-polypropylene interface, reduces the stress concentration inside the matrix, and limits the slippage and chain reorganization of the polypropylene molecular chain through physical barriers. Overall, the present invention uses carbon nanotube fillers and chopped glass fibers to synergistically reinforce the polypropylene resin matrix in multiple scales, significantly improving the overall mechanical properties of the fiber composite material.
[0025] 3. Toughening agent: Ethylene-octene copolymer is distributed in the continuous phase polypropylene matrix ("sea") in the form of microfibrillated particles ("islands"), forming a "sea-island" structure. 3,3',5,5'-tetramethylbenzidine induces the polypropylene matrix to form β crystals during the cooling process of melt blending, generating slender rod-shaped crystals. When subjected to impact damage, the uniformly distributed ethylene-octene copolymer particles in the brittle polypropylene matrix can evenly disperse the external impact stress on its spherical surface, reducing the stress acting on the brittle matrix. When the impact stress increases further, the toughening agent particles, as stress concentration areas, induce a large number of silver streaks and shear bands in the brittle matrix. This process absorbs a lot of energy, thereby achieving toughening and improving the impact resistance of the polypropylene resin matrix.
[0026] 4. The present invention has mild preparation conditions, a wide range of applications, and high product molding quality. The fiber composite material is secondary molded using a prepreg tape melt pultrusion process, which effectively improves the problem of difficulty in impregnation caused by the high viscosity of the polypropylene matrix in the molten state. At the same time, sufficient melting time eliminates most of the pores, cracks and other internal defects in the fiber composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The present invention is a flow chart of a high-strength and high-toughness carbon nanotube-modified polypropylene-based fiber composite material and a preparation method thereof.
[0028] Figure 2 These are the microscopic morphologies of the radial cross-section of the polypropylene-based fiber composite material before and after carbon nanotube modification, (a) before modification, (b) after modification. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0030] Embodiment 1:
[0031] In this embodiment, a reinforced and toughened carbon nanotube-modified polypropylene resin is synthesized. The amounts of each formula are as follows: 23.0 g of carbon nanotube filler, 92.0 g of polyvinyl pyrrolidone, 34.5 g of hexadecyltrimethylammonium bromide, 27.6 g of γ-aminopropyltriethoxysilane, 91.9 g of chopped glass fiber, 23.0 g of ethylene-octene copolymer, 1.8 g of 3,3',5,5'-tetramethylbenzidine, and 2180 g of maleic anhydride-grafted polypropylene.
[0032] Furthermore, the preparation of a polypropylene-based glass fiber composite rod using the carbon nanotube-modified polypropylene resin as described above comprises the following steps:
[0033] Step 1: preparing carbon nanotube reinforcement;
[0034] Step 2: preparing a reinforced and toughened polypropylene resin;
[0035] Step 3: preparing a polypropylene-based fiber composite material prepreg tape;
[0036] Step 4: Prepare polypropylene-based fiber composite materials.
[0037] Furthermore, in step 1, preparing a carbon nanotube reinforcement includes:
[0038] A formulated amount of polyvinyl pyrrolidone and a formulated amount of anhydrous ethanol are stirred and mixed, a formulated amount of carbon nanotube filler is added to the mixed solution, and ultrasonic dispersion is performed for 0.5 h under the assistance of ultrasound with a power of 200 W to obtain a carbon nanotube dispersion liquid I; a formulated amount of hexadecyltrimethylammonium bromide is added, and the carbon nanotube dispersion liquid I is dispersed by high-speed centrifugation at 10000 rpm for 20 min, and the carbon nanotube dispersion liquid II is allowed to stand to obtain a stratified carbon nanotube dispersion liquid II; the upper layer solution is extracted to obtain a carbon nanotube dispersion liquid III placed in a lower layer; the carbon nanotube dispersion liquid III is filtered with a membrane filter, and the precipitate is washed and dried to obtain a carbon nanotube reinforcement body IV.
[0039] Further, in step 2, preparing a reinforced and toughened carbon nanotube-modified polypropylene resin comprises:
[0040] The formulated amount of ethylene-octene copolymer, maleic anhydride grafted polypropylene and chopped fibers are added to a twin-screw extruder. The speed of the twin-screw extruder high-speed mechanical shearing and stirring is 2000 rpm, the stirring temperature is 230°C, and the nozzle temperature is 190°C. The carbon nanotube reinforcement IV is added by side feeding, and the carbon nanotube modified polypropylene resin V is obtained by melt blending and extrusion.
[0041] Furthermore, in step 3, preparing a polypropylene-based fiber composite material prepreg tape comprises:
[0042] Driven by the traction system, the continuous glass fiber passes through the yarn frame and is spread into continuous fiber monofilaments through dispersion, preheating desizing and yarn spreading treatment; the molten reinforced and toughened polypropylene resin V extruded by the twin-screw extruder is spread on the surface of the fiber filament, and the resin is impregnated into the fiber through a melt impregnation mold, and the heating temperature is set to 250°C; and the polypropylene-based fiber composite material prepreg tape VI is obtained through calendering treatment.
[0043] Preferably, in step 4, preparing the polypropylene-based fiber composite material rod comprises:
[0044] 23 bundles of 10mm wide polypropylene-based fiber composite prepreg tapes VI are driven by the traction system to pass through the yarn frame, heated and melted in the melting mold, and cooled to shape. The heating temperature and cooling temperature of the molding mold are 230℃ and 110℃ respectively, and the traction rate is 0.3m / min. The polypropylene-based fiber composite rod VII with a diameter of 10mm is obtained by pultrusion.
[0045] Embodiment 2:
[0046] In this embodiment, a reinforced and toughened carbon nanotube-modified polypropylene resin is synthesized. The amounts of each formula are as follows: 46.0 g of carbon nanotube filler, 92.0 g of polyvinyl pyrrolidone, 34.5 g of hexadecyltrimethylammonium bromide, 27.6 g of γ-aminopropyltriethoxysilane, 91.9 g of chopped glass fiber, 23.0 g of ethylene-octene copolymer, 1.8 g of 3,3',5,5'-tetramethylbenzidine, and 2180 g of maleic anhydride-grafted polypropylene.
[0047] Furthermore, a polypropylene-based glass fiber composite material rod is prepared by using the reinforced and toughened carbon nanotube-modified polypropylene resin as described above, and the specific implementation method is the same as that of Example 1.
[0048] Embodiment 3:
[0049] In this embodiment, a reinforced and toughened carbon nanotube-modified polypropylene resin is synthesized. The amounts of each formula are as follows: 11.5 g of carbon nanotube filler, 92.0 g of polyvinyl pyrrolidone, 34.5 g of hexadecyltrimethylammonium bromide, 27.6 g of γ-aminopropyltriethoxysilane, 91.9 g of chopped glass fiber, 23.0 g of ethylene-octene copolymer, 1.8 g of 3,3',5,5'-tetramethylbenzidine, and 2180 g of maleic anhydride-grafted polypropylene.
[0050] Furthermore, a polypropylene-based glass fiber composite material rod is prepared by using the reinforced and toughened carbon nanotube-modified polypropylene resin as described above, and the specific implementation method is the same as that of Example 1.
[0051] Comparative Example 1:
[0052] This comparative example provides a polypropylene-based fiber composite material that is not modified with carbon nanotubes, wherein the resin matrix is only maleic anhydride grafted polypropylene. The specific implementation method is the same as step 3 and step 4 of example 1.
[0053] Comparative Example 2:
[0054] This comparative example adopts the same implementation method as Example 1 to synthesize a reinforced and toughened carbon nanotube modified polypropylene resin, except that short chopped glass fibers are not added. The dosage of each formula is as follows: 23.0 g of carbon nanotube filler, 92.0 g of polyvinyl pyrrolidone, 34.5 g of hexadecyltrimethylammonium bromide, 27.6 g of γ-aminopropyltriethoxysilane, 23.0 g of ethylene-octene copolymer, 1.8 g of 3,3',5,5'-tetramethylbenzidine, and 2180 g of maleic anhydride grafted polypropylene.
[0055] Furthermore, a polypropylene-based glass fiber composite rod is prepared by using the reinforced and toughened carbon nanotube-modified polypropylene resin as described above. The specific implementation method is the same as step 3 and step 4 of embodiment 1.
[0056] Comparative Example 3:
[0057] This comparative example adopts the same implementation method as Example 1 to synthesize a reinforced and toughened carbon nanotube modified polypropylene resin, except that ethylene-octene copolymer and 3,3',5,5'-tetramethylbenzidine are not added. The dosage of each formula is as follows: 23.0g carbon nanotube filler, 92.0g polyvinyl pyrrolidone, 34.5g hexadecyltrimethylammonium bromide, 27.6g γ-aminopropyltriethoxysilane, 91.9g chopped glass fiber, and 2180g maleic anhydride grafted polypropylene.
[0058] Furthermore, a polypropylene-based glass fiber composite rod is prepared by using the reinforced and toughened carbon nanotube-modified polypropylene resin as described above. The specific implementation method is the same as step 3 and step 4 of embodiment 1.
[0059] The tensile properties, bending properties and short beam shear properties of the polypropylene-based fiber composite material were tested. The test results of the mechanical properties are shown in Table 1.
[0060] Table 1 Performance test results of high-strength and high-toughness carbon nanotube-modified polypropylene-based fiber composites
[0061]
[0062] From the above, it can be seen that the present invention uses carbon nanotube fillers and short glass fibers to synergistically reinforce the polypropylene matrix in multiple scales, effectively achieving the improvement of the mechanical strength of the fiber composite material. Compared with Comparative Example 1, the tensile strength, bending strength, and short beam shear strength of Example 1 increased by 12.4%, 11.8%, and 10.6%, respectively, with an increase of more than 10%, indicating that the carbon nanotube fillers are uniformly dispersed through surface modification and grafting, promoting the improvement of the rigidity of the polypropylene matrix, and the macroscopic performance is the enhancement of the mechanical strength of the fiber composite material; the mechanical index of Example 2 is slightly lower than that of Example 1, which is due to the fact that too much carbon nanotube filler agglomerates in the polypropylene matrix and is difficult to disperse; the elongation at break of each group of examples is significantly higher than that of Comparative Example 3, indicating that the synergistic effect of ethylene-octene copolymer and 3,3',5,5'-tetramethylbenzidine achieves high toughness of the polypropylene resin matrix. Figure 2 The microscopic morphology of the radial cross-section of the fiber composite rod before and after modification shows that the defects inside the fiber composite are significantly reduced after modification, and the degree of fiber impregnation is improved, indicating that the high-strength and high-toughness modification significantly improves the molding quality of the fiber composite.
[0063] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the claims of the present invention.
Claims
1. A reinforced and toughened carbon nanotube-modified polypropylene resin, characterized in that: The preparation is carried out according to the following steps, wherein the formula is calculated by weight: 0.5-2 parts of carbon nanotube filler, 1-6 parts of polyvinyl pyrrolidone, 0.5-2 parts of hexadecyltrimethylammonium bromide, 0.5-1.5 parts of γ-aminopropyltriethoxysilane, 2-6 parts of chopped glass fibers, 1-3 parts of ethylene-octene copolymer, 0.05-0.15 parts of 3,3',5,5'-tetramethylbenzidine and 90-100 parts of maleic anhydride grafted polypropylene. Step S1: preparing a carbon nanotube reinforcement: polyvinyl pyrrolidone, γ-aminopropyl triethoxysilane and anhydrous ethanol are stirred and mixed according to a ratio, carbon nanotube filler is added to the mixed solution, and ultrasonic treatment is used to obtain a uniform mixed solution to obtain a carbon nanotube dispersion liquid I; hexadecyl trimethyl ammonium bromide is added, and the carbon nanotube dispersion liquid I is dispersed by high-speed centrifugation, and allowed to stand to obtain a stratified carbon nanotube dispersion liquid II; the upper layer solution is extracted to obtain a carbon nanotube dispersion liquid III placed in a lower layer; the carbon nanotube dispersion liquid III is filtered through a membrane filter, and the precipitate is washed and dried to obtain a carbon nanotube reinforcement body IV modified by adsorption of hexadecyl trimethyl ammonium bromide; Step S2: preparing a reinforced and toughened carbon nanotube-modified polypropylene resin: adding ethylene-octene copolymer, maleic anhydride grafted polypropylene, chopped glass fiber, and 3,3',5,5'-tetramethylbenzidine into a twin-screw extruder according to a proportion, uniformly mixing them in the hopper of the twin-screw extruder, and adding the carbon nanotube reinforcement IV, and obtaining a reinforced and toughened carbon nanotube-modified polypropylene resin through melt blending and extrusion.
2. The reinforced and toughened carbon nanotube-modified polypropylene resin according to claim 1, characterized in that: The carbon nanotube filler is a carboxyl carbon nanotube with a size of 5-20 nm; the particle size range of the chopped glass fiber is 10-50 μm.
3. A reinforced and toughened carbon nanotube-modified polypropylene resin as claimed in claim 1, characterized in that: In step S1, the power of ultrasound is 200-400 W, the time is 0.5-1 h, the centrifugal dispersion time is 10-60 min, and the centrifugal speed is 8000-20000 rpm.
4. The reinforced and toughened carbon nanotube-modified polypropylene resin according to claim 1, characterized in that: In step S1, the upper layer solution of the carbon nanotube dispersion II is anhydrous ethanol, and the lower layer solution is a mixed dispersion of carbon nanotube filler, hexadecyltrimethylammonium bromide and polyvinyl pyrrolidone; the carbon nanotube reinforcement IV is obtained by washing the precipitate obtained by filtering the carbon nanotube dispersion II with distilled water, and then drying it at 25-80°C for 18-30h.
5. The reinforced and toughened carbon nanotube-modified polypropylene resin according to claim 1, characterized in that: In step S2, the main screw speed of the twin-screw extruder is 100-300rpm, the feeding screw speed is 10-50rpm, the extrusion temperature during the extrusion process adopts a temperature combination with a temperature range of 190-240°C and increasing in sequence, and the head temperature is 190-200°C.
6. The reinforced and toughened carbon nanotube-modified polypropylene resin according to claim 1, characterized in that: In step S2, the ethylene-octene copolymer is distributed in the continuous phase polypropylene matrix in the form of microfibrillated particles, and 3,3',5,5'-tetramethylbenzidine induces the polypropylene matrix to form β crystals during the cooling process of melt blending, generating slender rod-shaped crystals; when subjected to impact damage, the external impact stress is evenly diffused along the toughening particles, so that the stress acting on the brittle polypropylene matrix is reduced, and a large number of silver streaks and shear bands are induced in the matrix, thereby absorbing most of the impact kinetic energy, and achieving matrix toughening of the fiber composite material.
7. A prepreg tape for preparing a polypropylene-based fiber composite material prepared by a reinforced and toughened carbon nanotube-modified polypropylene resin according to any one of claims 1 to 5, characterized in that: The preparation method is as follows: continuous fibers are driven by a traction system to pass through a yarn frame, and are dispersed into continuous fiber monofilaments through dispersion, preheating, desizing, and yarn spreading treatment; the molten reinforced and toughened carbon nanotube-modified polypropylene resin extruded by a twin-screw extruder is spread on the surface of the fiber filaments, and the resin is impregnated into the fiber through a melt impregnation mold; and a polypropylene-based fiber composite material prepreg tape is obtained through calendering treatment.
8. A polypropylene-based fiber composite material prepreg tape according to claim 7, characterized in that: The continuous fiber is glass fiber, carbon fiber or basalt fiber, the heating melting temperature is 200-300°C, and the pulling speed is 0.1-1m / min.
9. A polypropylene-based fiber composite material prepared from a polypropylene-based fiber composite material prepreg tape according to claim 7, characterized in that: The preparation method is as follows: the polypropylene-based fiber composite material prepreg tape is driven by a traction system to pass through a creel, heated and melted in a melting mold, cooled and shaped, and pultruded to obtain a polypropylene-based fiber composite material.
10. A polypropylene-based fiber composite material according to claim 9, characterized in that: The temperature used for molding is 200–300°C, the temperature used for cooling is 80–150°C, and the pulling speed is 0.1–1m / min.
Citation Information
Patent Citations
Anti-ageing impact-resistant modified polypropylene material and preparation method thereof
CN108794885A
Carbon nanotube-reinforced polypropylene composite material and preparation method thereof
CN109608669A
High-toughness two-dimensional ultra-thin titanium oxide modified PP nano composite material and a preparation method thereof
CN109796679A
Preparation method of carbon nano-tube / polypropylene composite material
CN101012329A
Nano-particle and elastomer reinforcing and toughening polypropylene composite material and preparation method thereof
CN103146060A
Cited By
Marble flow line color master batch and preparation method thereof
CN120005308A
Multi-scale filler synergistically enhanced polypropylene composite material and preparation method thereof
CN122145926A